Enhancing retention of occupational therapists working in mental health: Relationships between wellbeing at work and turnover intention. Issue 6 (1st September 2013) - Scanlan, Justin Newton; Meredith, Pamela; Poulsen, Anne A.
<x xml:space="preserve">Abstract</x> Background/aim Occupational therapists working in mental health who experience burnout, low work engagement or poor job satisfaction are at risk of poor wellbeing at work and may be more likely to leave their jobs. The aim of this project was to explore factors associated with wellbeing at work and turnover intention in a sample of occupational therapists working in mental health. Methods One hundred and three occupational therapists working in mental health in Queensland completed a survey exploring work/life balance, effort invested in work, rewards received from work, wellbeing at work (job satisfaction, burnout and work engagement) and turnover intention. Analyses were conducted to explore relationships between work/life balance, effort, reward, wellbeing at work and turnover intention. Results All measures of wellbeing at work were significantly associated with turnover intention. A large proportion (33%) of the variance in turnover intention was predicted by job satisfaction. Perceptions of both work/life balance and effort invested in work, as well as perceived rewards in terms of recognition, prestige and personal satisfaction were significantly associated with work‐related wellbeing scores. Conclusions and significance of the study Results from this study deepen the understanding of factors associated with wellbeing at work and turnover intention for occupational therapists in mental health. This knowledge will support the development of interventions aimed at reducing turnover intention and enhancing retention of occupational therapists in the mental health workforce.